The effect of income inequality on nutritional outcomes: Evidence from rural China - Jian Liu; Yanjun Ren; Thomas Glauben (Journal of New Economy, 2021)
There are growing concerns about income inequality and health, while little is known about the relationship between income inequality and nutritional outcomes, especially in a transition economy like China. To fill this gap, the aim of this study is to explore the effect of income inequality on the nutritional outcomes of Chinese farmers, including body mass index (BMI), underweight, overweight and obesity statuses. Methodologically this study relies on the theoretical propositions of both income hypothesis and agricultural economics. Specifically, this study compares the literature examining income inequality, then analyses the possible effects of income inequality on the nutritional outcomes of Chinese farmers, and finally tests the results of the analysis using econometric models. Using data from the China Health and Nutrition Survey (CHNS) from 2015, we found that the relationship between income and BMI shifted from positive to negative with rapid growth in per capita household incomes and that higher income inequality can significantly increase the risk of being overweight or obese among low-income groups. In particular, the effect of income inequality on overweight and obesity is higher for males, while its effect tends to be negligible for females. The findings in this study are proved to be robust. Therefore, several policy implications for meeting the challenges concerning income inequality and improving nutritional outcomes for Chinese farmers are also discussed.
Keywords: D63; I10; O15; 630; income inequality; rural development; nutritional outcomes; body mass index (BMI); population health; transition economy; China